2003
DOI: 10.1046/j.0737-1209.2003.20306.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Infant Outcomes at One Year for a Nurse‐Health Advocate Home Visiting Program Serving African Americans and Mexican Americans

Abstract: This article describes the outcomes at 1 year for a randomized clinical trial of Resources, Education and Care in the Home-Futures: a program to reduce infant mortality through home visits by a team of trained community residents led by a nurse. Low-income, inner-city pregnant women who self-identified as African American or Mexican American were recruited in two university prenatal clinics in Chicago. Because African Americans and Mexican Americans differed greatly at intake, we compared their outcomes at 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 52 publications
1
53
0
Order By: Relevance
“…Community outreach workers or paraprofessionals working as community advocates have been shown to have a positive effect on outcomes for selected populations of childbearing women (Norr et al, 2003). Models promoting the combination of these roles have received little research attention in the literature, but they represent an opportunity to maximize the positive effect of social support as an intervention to promote positive health outcomes for childbearing women and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Community outreach workers or paraprofessionals working as community advocates have been shown to have a positive effect on outcomes for selected populations of childbearing women (Norr et al, 2003). Models promoting the combination of these roles have received little research attention in the literature, but they represent an opportunity to maximize the positive effect of social support as an intervention to promote positive health outcomes for childbearing women and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, studies with human infants have supported the benefits of intervention/ stimulation on developmental outcome of children from impoverished backgrounds, as well as on high-risk children such as premature infants and drug-exposed infants (e.g. Fazzi et al, 1997;Norr et al, 2003;Parker, Zahr, Cole, & Brecht, 1992;Schuler, Nair, & Kettinger, 2003;Zigler & Muenchow, 1992). Therefore, a rich environment with intensive stimulation may well allow infants with brain injury to recover.…”
mentioning
confidence: 99%
“…However, less encouraging results were reported by Barnet et al (2007), ElKamary et al (2004), Koniak-Griffin et al (2002, Norr et al (2003), and Stevens-Simon et al (2001). The results of these studies are summarized in Table 2.…”
Section: Effectiveness Of Home Visitation Programs In Preventing Rrbsmentioning
confidence: 77%
“…Specifically, Koniak-Griffin et al (2002, due to small sample sizes, failed to achieve statistically significant results despite finding a nearly 50% reduction in rates of RRB and TRB among participants. Similarly, Norr et al (2003) reported that their results may have been distorted by a basal effect in that repeat pregnancy rates were so low across all intervention and control groups that they left little room for improvement.…”
Section: Critiquementioning
confidence: 93%
See 1 more Smart Citation